Anti‐CO Poisoning FePtRh Nanoflowers with Rh‐Rich Core and Fe‐Rich Shell Boost Methanol Oxidation Electrocatalysis. (8th December 2022) - Liu, Hu; Jia, Rongrong; Qin, Chuanjian; Yang, Qin; Tang, Zuobin; Li, Menggang; Ma, Zhenhui
Abstract: Introducing oxophilic metals into Pt‐based alloy catalysts can effectively alleviate the poisoning by CO intermediates (CO*) during methanol oxidation reactions (MOR). However, excessive oxophilic metals on the surface of catalysts tend to form thermodynamically stable carbonyl compound‐like structures, occupying electrocatalytically active sites, which is not conducive to the enhancement of catalytic activity. Herein, a kind of surface segregated FePtRh nanoflowers for effectively eliminating the CO* poisoning during MOR electrocatalysis is presented. The FePtRh nanoflowers are constituted by the Rh‐rich core and Fe‐rich shell. The optimized Fe21 Pt66 Rh13 /C shows a high mass activity of 3.90 A mgPt −1 and a specific activity of 4.85 mA cm −2 . It is confirmed that the electron transfer from Pt to Rh or Fe atoms is beneficial for the higher anti‐CO poisoning ability, which mainly originate from the alloying of Rh atoms and surface‐segregated structures. Density functional theory calculations reveal the decreased electrons adsorbed by CO* on both Pt–Pt bridge sites and top sites weakens the strong adsorption energy between Pt atoms and CO* intermediates. The optimal nanoflowers also show excellent performance toward ethanol oxidation reaction (EOR) with a high mass activity of 2.76 A mgPt −1 and the enhanced anti‐CO poisoning ability, as well as the improved stability. Abstract : Alleviating the Pt‐based alloy catalysts poisoning by CO intermediates is significant for methanol oxidation reactions. Novel FePtRh nanoflowers with the Rh‐rich core and Fe‐rich shell are reported to effectively eliminate the CO intermediate poisoning during methanol oxidation reaction electrocatalysis with high mass activity and specific activity. This work offers a new way to design efficient Pt‐based alloy catalysts.